(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
We can accsess true the data of Tropical Peatland Plantation - Carbon Assessment Tool (Tropp-CAT) model using Microsoft Excel sofware. This model evaluated and predicted the loss of soil carbon and CO2 emissions from tropical peat lands. This research was using the carbon balance calculations following the Tropp-CAT model steppeds, by adding the carbon stocks above and below ground data on oil palm plantations on peatlands. Total carbon stored in the local research area for 733.95 ha is 17394.17 t CO2. Stocks carbon was calculated for palm oil 11, 16, 18 and 21 years is 12.732, 17.906, 20.507, 20.5737 t CO2 ha-1 year-1 respectly. Stocks carbon was calculated for peat at a depth 0-30 and 0-60 cm is 1 469.50 and 3 270.06 t CO2 ha-1respectly. Rainfall average is 122 mm year-1 with 8 days of rain. High ground water level in the main trend and the branch respectively -61.24 and -60.86 cm with emissions rate 43.96 and 44.12 t CO2 ha-1 respectively. Calculation of water content at a depth of 0-30 and 30-60 cm respectively 379% and 419%. The moisture content of the soil influence the CO2 and CH4 emissions. The higher water content of soil, affected lowest emissions peat soil. Research for the primer and secondary drainase based on moisture content was 1.272,46 and 1.150, t CO2 ha-1. The conclution is: (1) oil palm aging increased carbon sequestered and a net absorption of CO2 from the atmosphere by plants, (2) soil is greater than the release of CO2 due to emissions.